2012
DOI: 10.1186/1744-9081-8-52
|View full text |Cite
|
Sign up to set email alerts
|

Fear conditioning-related changes in cerebellar Purkinje cell activities in goldfish

Abstract: BackgroundFear conditioning-induced changes in cerebellar Purkinje cell responses to a conditioned stimulus have been reported in rabbits. It has been suggested that synaptic long-term potentiation and the resulting increases in firing rates of Purkinje cells are related to the acquisition of conditioned fear in mammals. However, Purkinje cell activities during acquisition of conditioned fear have not been analysed, and changes in Purkinje cell activities throughout the development of conditioned fear have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, the suppression of simple spikes of Purkinje-cell activity during eyeblink conditioning in mammals is also reported 42 , 43 . Although fear conditioning in goldfish increases the simple spikes in some Purkinje cells, more of these cells show a reduction in simple spikes 44 , suggesting that in teleosts, Purkinje-cell activity is mostly suppressed during fear conditioning. The reduced Purkinje-cell activity probably upregulates the activity of the projection neurons, which may be responsible for expressing the conditioned fear responses.…”
Section: Discussionmentioning
confidence: 97%
“…However, the suppression of simple spikes of Purkinje-cell activity during eyeblink conditioning in mammals is also reported 42 , 43 . Although fear conditioning in goldfish increases the simple spikes in some Purkinje cells, more of these cells show a reduction in simple spikes 44 , suggesting that in teleosts, Purkinje-cell activity is mostly suppressed during fear conditioning. The reduced Purkinje-cell activity probably upregulates the activity of the projection neurons, which may be responsible for expressing the conditioned fear responses.…”
Section: Discussionmentioning
confidence: 97%
“…We found that the IO is not associated with nociceptive reflexes in the tail-flick test but is important in the tachycardiac response to the US. A previous study on the acquisition of fear-conditioned bradycardia in goldfish found that cerebellar Purkinje cells have a simple spike response to the CS and complex spike response to the US 21 . Thus, inputs from the IO to the cerebellar cortex and/or cerebellar nuclei are thought to be involved in tachycardiac responses to the US.…”
Section: Discussionmentioning
confidence: 97%
“…Adult teleost fish classically condition readily (Agranoff and Davis, 1968; Flood et al, 1976; Amiro and Bitterman, 1980; Mattioli et al, 1998; Eisenberg et al, 2003; Salas et al, 2006; Yoshida and Kondo, 2012), and there have been several published reports of classical conditioning in adult zebrafish (Braubach et al, 2009; Agetsuma et al, 2010; Karnik and Gerlai, 2012; Aoki et al, 2013). To date, there have been just two reports of successful classical conditioning in larval to juvenile zebrafish.…”
Section: Types Of Learning and Memory In Larval Zebrafishmentioning
confidence: 99%